2024
DOI: 10.1039/d3py01265d
|View full text |Cite
|
Sign up to set email alerts
|

A flexible solid-state electrolyte based on comb-like PEG-functionalized covalent organic frameworks for lithium metal batteries

Xueling Tan,
Yongfen Tong,
Jiansong Yang
et al.

Abstract: Solid-state batteries have great potential for increased safety and energy density, but most solid-state electrolytes show relatively low ionic conductivity and can’t fully meet the requirements of solid-state batteries. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Tan et al incorporated poly(ethylene glycol) methyl ether methacrylate (PEGMA) in the ethylene-based COF (Bt-COF) channels and successfully prepared a homogeneous composite solid polymer electrolyte (Bt-COF x% -SPE) (Figure 9d). [69] When 2 % content of Bt-COF was used, the crystallinity of PEGMA was decreased and the surface of the formed electrolyte membrane was smooth and dense (Figure 9e). Moreover, the Bt-COF-contained electrolytes exhibited a high ionic conductivity of 5.3×10 À 5 S cm À 1 (vs. 1.2×10 À 6 S cm À 1 for Bt-COF-free electrolytes; Table 4) and a satisfying t Li + (0.47) at room temperature (Figure 9f, g).…”
Section: Lmbs Zibs Rmbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tan et al incorporated poly(ethylene glycol) methyl ether methacrylate (PEGMA) in the ethylene-based COF (Bt-COF) channels and successfully prepared a homogeneous composite solid polymer electrolyte (Bt-COF x% -SPE) (Figure 9d). [69] When 2 % content of Bt-COF was used, the crystallinity of PEGMA was decreased and the surface of the formed electrolyte membrane was smooth and dense (Figure 9e). Moreover, the Bt-COF-contained electrolytes exhibited a high ionic conductivity of 5.3×10 À 5 S cm À 1 (vs. 1.2×10 À 6 S cm À 1 for Bt-COF-free electrolytes; Table 4) and a satisfying t Li + (0.47) at room temperature (Figure 9f, g).…”
Section: Lmbs Zibs Rmbsmentioning
confidence: 99%
“…h) Cycling performance of LFP j j Bt-COF 2% -SPE j j Li cell. [69] Copyright 2024, Royal Society of Chemistry. lyte (HGPE) is conducive to the performance and safety of batteries (Figure 10a).…”
Section: Lmbs Zibs Rmbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Filling polyethylene glycol (PEG) into the pores of covalent organic frameworks (COFs) can improve the stability of COF significantly. 18–22 In 2021, Ting Zhou et al reported that the structure of BT-COF filled with PEG (BT-COF@PEG) was more stable, and its hydrogen evolution rate was 1.44 times that of BT-COF without PEG, indicating that the addition of PEG could also increase the photocatalytic hydrogen evolution rate. 20 As an important member of the COF family, CTFs may show high crystallinity and stability by PEG, so the optimal composite ratio should be explored in order to achieve higher photocatalytic hydrogen evolution performance.…”
Section: Introductionmentioning
confidence: 99%